Ethinylestradiol–levonorgestrel bait impairs testicular function, triggers germ cell apoptosis, and alters health markers in male rats: implications for wildlife fertility - Mikail, Muhammed; Raji, Abdullahi Abdullahi; Moses, Matilda Mening; Najib Paarthiban, Norlaila; DanMaigoro, Abubakar; Badrul Hisham, Nur Eizzati; Juha, Muhammad Faiz; Kamaruzzaman, Intan Noor Aina; Reduan, Mohd Farhan Hanif; Mohd Noor, Mohd Hezmee; Hassim, Hasliza Abu; Tengku Azizan, Tengku Rinalfi Putra (John Wiley and Sons, 2026)
Lethal rodent control methods raise ecological and ethical concerns, driving interest in fertility-based population management approaches. Hormonal male baiting represents an innovative ecological tool for rodent population control. While most studies have focused on quinestrol+ levonorgestrel (EP1), there have been few studies of alternative hormones. To date, no study has investigated the palatability, hematology, or serum biochemistry effects of ethinylestradiol–levonorgestrel (EE + LNG) bait on male rats nor have there been studies on the integrity of the testes, liver, and kidney using acridine orange/propidium iodide (AO/PI), 4′,6-diamidino-2-phenylindole (DAPI), and hematoxylin & eosin (H & E) staining histopathology. We evaluated the toxicological and antifertility effects of an EE + LNG bait in male rats. We used 18 adult male rats (n = 18) divided into control, the low-dose, and high-dose groups (n = 6/group). Each male rat received Baits A and B for 7 days. Daily consumption was recorded as g/kg/day. Blood samples were collected for complete blood count, serum biochemistry, and serum testosterone analysis. We evaluated the integrity of the testes, liver, and kidney tissues through H & E, DAPI, and AO/PI staining. The results from the covariance (ANCOVA) indicated that the control group maintained the highest adjusted body weight (230.3 g), followed by the low-dose group (225.1 g) and the high-dose group (219.9 g), suggesting that EE + LNG bait may influence male body weight gain over time. The result from the mixed-design RM ANOVA showed a significant main effect of bait type, demonstrating that male rats consumed more of Bait A (M = 120.4 g/day) compared to Bait B (M = 72.3 g/day), indicating the higher palatability of Bait A. EE + LNG consumption resulted in dose-dependent suppression of serum testosterone, accompanied by reduced testicular and epididymal weights, degenerative histopathological changes, and marked germ cell apoptosis particularly in the high-dose group. Hematological and serum biochemical analysis demonstrated statistically significant changes in red blood cell indices and liver enzyme activity, consistent with sublethal systemic toxicity. H & E, DAPI, and AO/PI staining confirmed nuclear damage, apoptosis, and necrosis in testicular, hepatic, and renal tissues. This study provides the first evidence that EE + LNG bait is readily consumed by male rats and exerts potent anti-androgenic and reproductive toxic effects, accompanied by measurable systemic and tissue-level toxicity. While the observed changes were nonlethal over the short exposure period, they indicate biologically active endocrine disruption rather than physiological safety. These findings extend hormonal bait research beyond EP-1 formulations and highlight the importance of risk–benefit evaluation when considering EE + LNG bait as a fertility control tool. We conclude that Bait A is better positioned to deliver an effective contraceptive dose to rodents, supporting their potentials for developing a humane, bait-delivered fertility control approach to mitigate ecological and public health impacts of overabundant populations.